Essential Role of Zinc and Zinc Transporters in Myeloid Cell Function and Host Defense against Infection. (17th October 2018) - Sapkota, Muna; Knoell, Daren L.
Abstract : Zinc is an essential micronutrient known to play a vital role in host defense against pathogens. Diets that are deficient in zinc lead to impaired immunity and delayed recovery from and worse outcomes following infection. Sustained insufficient zinc intake leads to dysregulation of the innate immune response and increases susceptibility to infection whereas zinc supplementation in at-risk populations has been shown to restore host defense and reduce pathogen-related morbidity and mortality. Upon infection, zinc deficiency leads to increased pathology due to imbalance in key signaling networks that result in excessive inflammation and collateral tissue damage. In particular, zinc impacts macrophage function, a critical front-line cell in host defense, in addition to other immune cells. Deficits in zinc adversely impact macrophage function resulting in dysregulation of phagocytosis, intracellular killing, and cytokine production. An additional work in this field has revealed a vital role for several zinc transporter proteins that are required for proper bioredistribution of zinc within mononuclear cells to achieve an optimal immune response against invading microorganisms. In this review, we will discuss the most recent developments regarding zinc's role in innate immunity and protection against pathogen invasion.